Errors made by students of Iraqi college level in the area of phrasal verbs - Al-sadi, Zainab Abbas; AbdulMehdi, Ashwaq (Al-Adab Journal, 2021)
The present study aims at finding out the difference in the number of errors made by the students at the college level in relation to the use of idiomatic and literal phrasal verbs. To achieve this aim, a test of 30 items has been conducted to a sample of 150 students at college of Education, English department, University of Diyala. After analyzing the data statistically, it has been found out that the number of errors committed in the recognition part is nearly similar to that of the production one and the students have committed more errors in the use of the phrasal verbs that have idiomatic meaning.